2001
DOI: 10.1042/0264-6021:3540591
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporin A reduces canalicular membrane fluidity and regulates transporter function in rats

Abstract: Changes of the biliary canalicular membrane lipid content can affect membrane fluidity and biliary lipid secretion in rats. The immunosuppressant cyclosporin A is known to cause intrahepatic cholestasis. This study investigated whether cyclosporin A influenced canalicular membrane fluidity by altering membrane phospholipids or transporter expression. In male Sprague-Dawley rats, a bile-duct cannula was inserted to collect bile, and sodium taurocholate was infused (100 nmol/min per 100 g) for 60 min. During ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 43 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…Although there are numerous data about the lithogenic characteristics of a CsA-based immunosuppressive therapy in animal studies [ 2 , 4 - 6 , 12 - 14 ], as well as in transplanted patients [ 1 , 15 ], clinical studies of hepatobiliary complications using Tac, which is similarly metabolized like CsA, are rare. Most animal model studies showed no or only mild lithogenic effects of Tac compared with CsA [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there are numerous data about the lithogenic characteristics of a CsA-based immunosuppressive therapy in animal studies [ 2 , 4 - 6 , 12 - 14 ], as well as in transplanted patients [ 1 , 15 ], clinical studies of hepatobiliary complications using Tac, which is similarly metabolized like CsA, are rare. Most animal model studies showed no or only mild lithogenic effects of Tac compared with CsA [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is a neutral highly lipophilic cyclic peptide and a potent immunosuppressant which has contributed significantly to improvements in organ transplantation but also causes various toxic effects in the kidney and the liver . CsA inhibits biliary bile acid secretion, and inhibition of the secretion of biliary components such as phospholipids, cholesterol, and bilirubin has also been reported. CsA, a multidrug resistance-1 protein (MDR1) substrate, may cause cholestatic liver injury through a number of mechanisms, , namely, (I) competitive inhibition of ATP-dependent transporters, (II) inhibition of intrahepatic vesicle transport and targeting of ATP-dependent transporters to the canalicular membrane, ,, and (III) impairment of bile formation partly by increasing canalicular membrane fluidity without affecting the expression of canalicular transporters . Other studies suggest that CsA reduces the expression of glutathione synthesizing enzymes and the canalicular glutathione efflux system, multidrug resistance-associated protein 2 (MRP2), leading to reduced bile acid-independent bile flow …”
Section: Introductionmentioning
confidence: 99%
“…Bsep is correctly localized, its intrinsic transport activity is selectively inhibited. Although an increase in membrane cholesterol could be beneficial because it improves its localization in lipid raft microdomains, excessive cholesterol content decreases J o u r n a l P r e -p r o o f canalicular membrane fluidity [52], a factor thought to influence Bsep transport activity [53,54]; this may explain the somewhat lower Bsep-mediated transport of the exogenously administered TC in the SL alone group (see Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
“…The 'rigidizing' effect of SL could be particularly detrimental in endotoxemic rats, since LPS per se reduces hepatocellular membrane fluidity by increasing the cellular influx of Ca 2+ [55], an effect that would add to the 'rigidizing' effect of SL itself, which may further decrease plasma membrane fluidity by alternative mechanisms associated with its effect as an aldosterone antagonist or as an estrogen-mimetic compound [46]. Unlike Bsep, circumstantial evidence suggest that Mrp2 transport function is scantily influenced by diminutions of plasma membrane fluidity [54], thus explaining the lack of impairment in DBSP biliary excretion when SL was administered alone (see Fig. 1), and the good relationship between improved localization and enhanced function observed for Mrp2 in SL+LPS co-treated group (see Figs.…”
Section: Discussionmentioning
confidence: 99%